Caracterización de las entidades o instituciones de servicios financieros mediadas por tecnología (Fintech) en Colombia entre los años 2008 a 2024 (2025)
Research on the technological transformation of Fintechs in Colombia reveals a constantly evolving landscape where innovation and digitalization play a crucial role in the development of the financial sector. This study focuses on how Fintechs, by offering accessible financial services, have facilitated the inclusion of segments of the population that have traditionally been excluded, contributing to a significant change in market dynamics. Through an exhaustive analysis of business models and emerging technologies, various strategies that these companies have implemented are identified, such as digital payment applications, microfinance platforms and automated savings solutions.